Effect of endogenous proteins and lipids on starch digestibility in rice flour. (April 2018) - Ye, Jiangping; Hu, Xiuting; Luo, Shunjing; McClements, David Julian; Liang, Lu; Liu, Chengmei
Abstract: The composition and structure of the food matrix can have a major impact on the digestion. The aim of this work was to investigate the effects of endogenous proteins and lipids on starch digestibility in rice flour, with an emphasis on establishing the underlying physicochemical mechanisms involved. Native long-grain indica rice flour and rice flour with the lipids and/or proteins removed were subjected to a simulated digestion in vitro . A significant increase in starch digestibility was observed after removal of proteins, lipids, or both. The starch digestibility of the rice flour without lipids was slightly lower than that without proteins, even though the proteins content was about 10-fold higher than the lipids content. Microstructural analysis suggested that the proteins and lipids were normally attached to the surfaces of the starch granules in the native rice flour, thus inhibiting their contact with digestive enzymes. Moreover, the proteins and lipids restricted the swelling of the starch granules, which may have decreased their digestion by reducing their surface areas. In addition, amylose-lipid complex was detected in the rice flour, which is also known to slow down starch digestion. These results have important implications for the design of foods with improved nutritional profiles. Graphical abstract: Image 1 Highlights: Endogenous proteins and lipids decreased starch digestibility of indica rice flour. Proteins and lipids inhibited swelling of starch. Starch was surrounded by proteins and lipids. Lipids and starch formed amylose-lipid complex.